A pilot study of combined optical coherence tomography and diffusion tensor imaging method for evaluating microstructural change in the visual pathway of pituitary adenoma patients - Yanhua Pang; Zhi Tan; Wei Mo; Xinxin Chen; Jinfen Wei; Qing Guo; Qin Zhong; Jingxiang Zhong (BMC Ophthalmology, 2022)
Abstract Background RNFL thickness measured by optical coherence tomography (OCT) and visual pathway measured by diffusion tensor imaging (DTI) can be used to predict visual field recovery, respectively. However, the relationship between RNFL thickness and visual pathway injury in patients with pituitary adenoma (PA) remains unclear. This study aims to evaluate the combining DTI and OCT methods in observing the microstructural change in the visual pathway in patients with PA. Methods Twenty-nine patients who were diagnosed with PA were included in the study group, and 29 healthy subjects were included as the control group. OCT detected the thickness of circumpapillary retinal nerve fiber layer (CP-RNFL) and ganglion cell layer (GCL). DTI measured the values of fractional anisotropy (FA) and apparent diffusion coefficient (ADC). Correlation between CP-RNFL and GCL thickness and FA and ADC values was analyzed in the study group. Results Compared with the control group, the FA values of the bilateral optic nerve, chiasma, bilateral optic tract, and left optic radiation in the study group were reduced, and the ADC values of the bilateral optic nerve and optic chiasma were increased. Correlation analysis showed that the FA value of the optic chiasma was positively correlated with the average thickness of RNFL, the CP-RNFL thickness in the nasal and temporal retinal quadrants in both eyes, as well as the thickness of macular ring GCL in the nasal, supra, and inferior quadrants. The FA values of the optic nerve, optic chiasma, optic tract, and optic radiation were positively correlated with CP-RNFL thickness in the nasal and temporal quadrants. Conclusion Combined DTI and OCT can provide a comprehensive understanding of the microscopic changes in the structure and function of the whole visual pathway in patients with PA.